The grammar translation method and the development of the english productive skills among the students of 5th, 6th and 7th years of basic education at IV Centenario no. 1 school. academic period 2012-2013 - Cueva Prado, Laura Yanina (2014)
The research work entitled: “THE GRAMMAR TRANSLATION METHOD AND THE DEVELOPMENT OF THE ENGLISH PRODUCTIVE SKILLS AMONG THE STUDENTS OF 5TH, 6TH AND 7TH YEARS OF BASIC EDUCATION AT IV CENTENARIO No. 1 SCHOOL. ACADEMIC PERIOD 2012-2013”.The general objective was to identify the influence that the grammar translation method has on the development of the English productive skills. The “Scientific, Descriptive, Analytic-Synthetic and Hypothetic Deductive” methods were used to describe, analyze and synthesize the obtained information. The technique used was a survey, applied to the students and teachers of 5th, 6th and 7th, years of basic education at IV Centenario No.1 School. The important findings are that the Grammar Translation Method is used by the English teachers and their characteristics do not help to develop the English productive skills in the English language. Therefore, it has limited the students’ achievement is in the English language learning.